Place of death for people with dementia: A scoping review - Paula Hidalgo-Andrade; Alejandro Unda-López; Tania Pastrana (PLoS ONE, 2026)
Background Dementia is a global health concern that contributes significantly to severe health-related suffering and poses high demands on healthcare systems, patients, families, and caregivers. Caring for people with dementia should include all the stages of illness, including end-of-life care. Aim Given that the place of death is a crucial aspect of end-of-life care, we aimed to analyze the scientific literature on the place of death of individuals with dementia, the sociodemographic and contextual variables associated with it, and evidence-based suggestions to improve end-of-life care for people with dementia. Methods We conducted a scoping review in 19 databases in November 2023 and updated the search in February 2025, yielding 1590 and 660 sources of evidence, respectively. Manuscripts had to a) focus on the frequency of more than one place of death, b) include population with dementia, c) use administrative data, and d) be published in peer-reviewed primary sources to be included in this study. The procedure for searching the sources of evidence and data charting was based on the structured approach for conducting scoping reviews by Arksey and O’Malley. Pre-registration can be retrieved at https://doi.org/10.17605/OSF.IO/BVXMY . Results After screening, a total of 48 studies were included in this review. Results indicate a great variability in the place of death of people with dementia across different regions and settings. Overall, in Europe and North America, it was more common for people with dementia to die in long-term care facilities like care homes, nursing homes, and sheltered housing; in East Asia and the Pacific, medical facilities (i.e., hospitals, mental health facilities, and private clinics) were more common. Studies that showed trends also indicate an increase in long-term-care facilities and a decrease in medical facilities and homes as the place of death. Most studies were conducted in high-income countries, raising questions about the diverse factors that may influence the place of death, such as access to services and socioeconomic status. Discussion These results could inform decisions on allocating resources and training for end-of-life care for people with dementia. However, more research is needed to increase the representativeness of other world regions and understand other variables that influence the place of death.